Balanced Nutrition Optimizes the Growth and Development of School Age Children - Hadiyani, Wini (Universitas Pendidikan Indonesia, 2024)
Background : Schools, as sites of teaching and learning, are intended to evolve into Health Promotion Schools. Objective : This activity aim to provide balanced nutrition health education which can optimize growth and development in school-aged children. Methods : The method of activity is community empowerment, which is accomplished through a series of health promotion. Result : This activity is useful for increasing students' knowledge, attitudes and behavior who can implement my food plate with a balanced nutritional pattern. Health promotion also plays a vital part in shaping food environments and access to healthy options. Through initiatives like school meal programs, community gardens, and partnerships with local businesses, health promotion efforts can ensure nutritious foods are available and affordable for all children, regardless of socioeconomic status. Conclusion : The nurse in charge of the UKS should carry out regular health promotions.